Molecular Characterization of Two Known SRD5A2 Gene Variants in Mexican Patients With Disorder of Sexual Development - María Guadalupe, Ortiz-López; Katy, Sánchez-Pozos; Charmina, Aguirre-Alvarado; Vihko, Pirkko; Marta, Menjivar (Frontiers in Genetics, 2022)
Background. The 5a-reductase type 2 deficiency (5a-RD2) is a specific form of disorder of sexual development (DSD). Pathogenic variants in the SRD5A2 gene, which encodes this enzyme, are responsible for 46,XY DSD. Objective. Investigate the genetic aetiology of 46,XY DSD in two Mexican families with affected children. Material and methods. The SRD5A2 gene of the parents and affected children was screened in both families via polymerase chain reaction amplification, and DNA direct sequencing. The role of genetic variants in enzymatic activity was tested by site-directed mutagenesis. Results. Subject 1 presented two variants: p.Glu197Asp and p.Pro212Arg. Subject 2 was homozygous for the variant p.Glu197Asp. The two variants were reported in early studies. The directed mutagenesis study showed that the p.Glu197Asp and p.Pro212Arg variants lead to a total loss of enzymatic activity and, consequently, abnormal genitalia development in the patients. Conclusion. These results suggest that p.Glu197Asp and p.Pro212Arg are pathogenic variants that lead to the phenotypic expression of DSD. 5-RD2 is of extreme importance not only because of its frequency (it is rare) but also because of its significance in understanding the mechanism of androgen action, the process of sexual differentiation, and the factors that influence normal sexual behaviour.